2014
DOI: 10.1016/j.jval.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Nonadherence to Antihypertensive Drugs: A Systematic Review and Meta-Analysis

Abstract: Published studies have not found a strong association between low SES and nonadherence to antihypertensive medications. However, important limitations in the assessment of SES can be identified in virtually all studies. Future studies are required to ascertain whether a stronger association is observed when SES is determined by comprehensive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 71 publications
5
54
1
4
Order By: Relevance
“…Alsabbagh et al showed significant correlation of low adherence in therapy and patients' socio-economic conditions [7]. In our study this information was not described, although co-payment was high enough for medication purchase, which partly could provoke purchase of the prescribed medications.…”
Section: Int Conf Society Health Welfare 2014contrasting
confidence: 48%
See 1 more Smart Citation
“…Alsabbagh et al showed significant correlation of low adherence in therapy and patients' socio-economic conditions [7]. In our study this information was not described, although co-payment was high enough for medication purchase, which partly could provoke purchase of the prescribed medications.…”
Section: Int Conf Society Health Welfare 2014contrasting
confidence: 48%
“…Most common doctor related factors include communication skills, knowledge of language and skill of implement royalty. Such health care system associated factors as distance to doctor's praxis and pharmacy, and system of medication compensation also can effect adherence [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The sample characteristic moderator analyses suggested interventions were more effective for older, female, and middle- or upper-income subjects. These findings suggest different interventions need to be developed for men, younger subjects, and adults with limited income [161]. …”
Section: Discussionmentioning
confidence: 99%
“…7 Low SEP is one of the predictors of nonadherence to preventive therapies, including statins, although previous research has reported varying results on the strength of this association. 7,8 Several studies, 7,[9][10][11][12] yet not all, 13 have found low income to predict statin nonadherence. Results on the association between education and statin nonadherence are mixed: low education level has been associated with statin nonadherence, 9,10 but higher education has also been found to predict statin nonadherence 9,11,13 or there has been no association.…”
mentioning
confidence: 99%